Sistem Cerdas Pemantauan Kualitas Air dan Pembersihan Otomatis Berbasis IoT dengan Turbidity Sensor Menggunakan GPRS SIM900A Berbasis Android. - Mohammad Alfian Mudzakir; Lawrence Adi Supriyono; Agus Subandono (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
Water quality is a crucial factor in supporting life, especially in water storage systems used for domestic and industrial purposes. A common issue that arises is the degradation of water quality due to increased turbidity, which can pose health risks and reduce water utilization efficiency. This study aims to design and develop an intelligent Internet of Things (IoT)-based system capable of real-time water quality monitoring and automatic cleaning of water storage tanks when turbidity exceeds a predefined threshold. The system utilizes a turbidity sensor to detect water clarity levels, a SIM900A GPRS module for data communication, and an Android application for real-time data visualization to the user. Monitoring and cleaning processes are controlled by an Arduino microcontroller integrated with an SMS-based alert system and a mobile user interface. Test results show that the system accurately detects turbidity levels, transmits data in real-time to the Android app, and automatically activates the cleaning mechanism when necessary. Additionally, the system can send early warning notifications via text messages. Therefore, this system offers an effective and efficient solution for maintaining water quality in a sustainable manner and contributes to the application of IoT technologies in smart water resource management.